Análisis Diagnóstico De Percepción En Adultos Jóvenes Sobre Participación Política Y Voto Electrónico En México - Irma Leticia Chávez-Márquez; Liliana Álvarez-Loya; María del Carmen Gutiérrez-Diez; Oscar Alejandro Viramontes-Olivas (European Scientific Journal, ESJ, 2017)
Mexico is challenging the perfection of democracy exercised by the people through voting. The objective of the research was to determine the feasibility of the exercise of electronic voting in Mexico, according to the political perception of young adults. The analysis is focused in the persons between 25 to 46 years old. This is a segment of the population of great importance within the economically active population in Mexico, and by the number of voters in this range, they have great influence on the results of the elections. The work was done from an analysis of the database obtained from the territorial survey conducted nationwide by the Center for Social and Political Studies (CESOP) of the LXII Legislature of the Chamber of Deputies in Mexico between November 21 and December 2, 2014; 1,400 interviews were conducted with 18 senior citizens spread over 132 municipalities throughout the country. The results were grouped into two variables, the first being the Political Participation with three indicators and the second, the Electronic Vote with six indicators. Cronbach Alfa Coefficient was obtained, with a value of 0.715.To measure the internal consistency of the research work, a multivariate factor analysis was performed. The main results indicate that they have low interest in politics. Their intention to vote is high on the following elections. The majority believes that electronic voting, people would come with greater certainty to cast the vote.